Instagram sebagai media strategis WEPOSE Indonesia dalam memperkuat keterlibatan komunitas - Bella Avianda Putri; Pandu Mustikasari, Ratih (Universitas Garut, 2025)
Abstract This study aims to analyze the social media strategies implemented by the Instagram account @wepose.indonesia in enhancing community engagement. The objective of this research is to identify how content strategies, the use of interactive features, and regular evaluations can support the growth of audience engagement both in digital spaces and through direct social activities. WEPOSE Indonesia is a non-profit community actively engaged in empowering marginalized children in Surabaya, utilizing Instagram as the primary medium to disseminate information, foster interaction, and mobilize public participation. This study employs a descriptive qualitative approach with data collected through in-depth interviews and digital documentation, analyzed using Miles and Huberman’s model. The findings indicate that WEPOSE’s success in building engagement derives from structured content strategies, the use of interactive Instagram features such as Reels, Stories, Live, and Direct Messages, as well as routine evaluation through the Insight feature. These strategies reflect the application of the SOME (Share, Optimize, Manage, Engage) model, which supports participatory, responsive, and relevant two-way communication. Challenges such as limited human resources and team consistency are addressed through collaborative work systems and internal capacity strengthening. Audience participation extends beyond digital interactions, being manifested in the form of contributions as field volunteers. With an adaptive and human-centered approach, WEPOSE’s social media strategy successfully creates an inclusive digital space and serves as an effective model for other non-profit communities in fostering sustainable public engagement.. Keywords: Scial media strategy; community engagement; instagram; non-profit organization; digital communication. Abstrak Penelitian ini bertujuan untuk menganalisis strategi media sosial yang diterapkan oleh akun Instagram @wepose.indonesia dalam meningkatkan keterlibatan komunitas (community engagement). Tujuan penelitian ini adalah untuk mengetahui bagaimana strategi konten, penggunaan fitur interaktif, serta evaluasi rutin dapat mendukung peningkatan keterlibatan audiens, baik di ranah digital maupun aktivitas sosial secara langsung. WEPOSE Indonesia merupakan komunitas nirlaba yang aktif dalam pemberdayaan anak-anak marginal di Surabaya, dengan memanfaatkan Instagram sebagai media utama untuk menyebarkan informasi, membangun interaksi, dan menggerakkan partisipasi publik. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara mendalam dan dokumentasi digital, serta dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa keberhasilan WEPOSE dalam membangun engagement berasal dari strategi konten yang terstruktur, penggunaan fitur interaktif Instagram seperti Reels, Story, Live, dan DM, serta penerapan evaluasi rutin melalui fitur Insight. Strategi ini mencerminkan penerapan model SOME (Share, Optimize, Manage, Engage) yang mendukung komunikasi dua arah yang partisipatif, responsif, dan relevan. Tantangan seperti keterbatasan sumber daya manusia dan konsistensi tim diatasi melalui sistem kerja kolaboratif dan penguatan kapasitas internal. Partisipasi audiens tidak hanya terbatas di ruang digital, tetapi juga diwujudkan dalam bentuk kontribusi sebagai relawan lapangan. Dengan pendekatan yang adaptif dan humanis, strategi media sosial WEPOSE berhasil menciptakan ruang digital yang inklusif dan menjadi model efektif bagi komunitas nirlaba lainnya dalam membangun keterlibatan publik secara berkelanjutan. Kata-kata kunci: Strategi media sosial; community engagement; instagram; organisasi nirlaba; komunikasi digital.